Next generation computing technologies on computational intelligence : 4th International Conference, NGCT 2018, Dehradun, India, November 21-22, 2018, Revised selected papers /: 4th International Conference, NGCT 2018, Dehradun, India, November 21-22, 2018, Revised selected papers. (2019) - Unknown
No abstract available